PENGARUH FAKTOR KEUANGAN DAN NON KEUANGAN TERHADAP PERINGKAT OBLIGASI PADA PERUSAHAAN NON KEUANGAN YANG TERDAFTAR DI BEI PERIODE 2011-2015 - Heni Kurnia; Mukhtaruddin Mukhtaruddin; Emylia Yuniartie (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2016)
The purpose of this study is to examine and analyze whether the financial factors (liquidity, productivity, and bank debt) and non-financial factors (maturity and auditor reputation) effect on bond’s rating. This study is a hypothesis testing, with 11 companies enlisted in Indonesian Stock Exchange in 2011-2015, as the sample issuing bond and rated by PT. PEFINDO. The type of data used in this research was secondary data. The required data was obtained from the official website of Indonesian Stock Exchange and PT. PEFINDO, then it will be analyzed using logistic regression analysis and hypothesis testing using the chi-square test and wald test. From the results of the model summary, it shows the values of 0,354 or 35,4%, that means the contribution from liquidity variables, productivity, bank debt, maturity, and auditor reputation towards the ranked bonds are 35,4%, while the rest 64,4 % are described by other factors that are not included in this research.